Cardiac adaptation to high-level ice hockey training: Myocardial longitudinal strain-intraventricular hemodynamic coupling in elite female athletes - Yang, P.; Zhang, J.; He, B. (Sports Medicine and Health Science, 2026)
Background Enlargement of an athlete's heart results from sustained hemodynamic overload during intensive exercise. Elite female ice hockey athletes exhibit larger left ventricular (LV) dimensions than healthy controls, but intrinsic myocardial contractile characteristics and their coupling with intracardiac hemodynamics remain unclear. This study explored coordinated adaptations of myocardial strain and intraventricular pressure in elite female ice hockey athletes.